The Rhetoric of Friedman's Quantity Theory Manifesto - Thomas Mayer (University of California, Department of Economics, 1997)
In 1956 when Friedman published his ""The Quantity Theory of Money: A Restatement"" he faced a daunting task because of the widespread hostility to the quantity theory. This paper looks at the rhetoric (in the non-pejorative sense of the term) that he used to overcome this obstacle, and at some of the characteristics of the essay that contribute to its persuasiveness.
Keywords: 330